2018
DOI: 10.1055/s-0038-1626694
|View full text |Cite
|
Sign up to set email alerts
|

Gender Comparison of Medical Student Microsurgical Skills in a Laboratory Model

Abstract: This study shows that microsurgical skills of male and female medical students are similar. Equal opportunities in the eventual pursuit of the surgical specialties should be available regardless of gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Chiu et al found that women performed better on a virtual simulator [ 34 ]. In another study addressing the gender-dependent performance of microsurgical skills, no difference was registered between women and men [ 35 ]. In view of the fact that only 29% of our participants were women, the comparison is not meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…Chiu et al found that women performed better on a virtual simulator [ 34 ]. In another study addressing the gender-dependent performance of microsurgical skills, no difference was registered between women and men [ 35 ]. In view of the fact that only 29% of our participants were women, the comparison is not meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our study population consisted of residents who are motivated to learn and practice new skills. These were not simply medical students [23], volunteers or paid [14], like in the Schijven et al study [24], who showed that among four improvement profiles, innate aptitudes could be more or less well applied to the acquisition of skills, including a group who did not improve. In the literature on VR arthroscopy, several profiles of innate aptitude have been described, in particular two extreme groups: those who are very good as they have scores greatly above average, making up 7% [25] to 17% of the sample [24], and those who are very bad as they have scores clearly below the average, making up 12% [25] to 20% of the sample [24].…”
Section: Resident Motivation and Target Populationmentioning
confidence: 99%
“…The microsurgical skills of male and female medical students are similar. Thus, regardless of gender, equal opportunities in the eventual pursuit of the surgical specialties should be available (7) .…”
Section: Gender Gap In Medical Students and National Examination Of P...mentioning
confidence: 99%